Review of the Book: Trepavlov V.V., Belyakov A.V. Sibirskie tsarevichi v istorii Rossii [The Siberian Princes in the History of Russia] - D.N. Maslyuzhenko (Золотоордынское обозрение)
This article analyzes the new book by Russian historians V.V. Trepavlov and A.V. Belyakov dedicated to the Siberian princes and their role in national history. The first part of the book is dedicated to the struggle of Kuchum Khan and his descendants for revenge in Siberia and the restoration of the Siberian Khanate, and the second one – to the conditions of the Kuchumovichi’s appearances in the Moscow state, their inhabitancy, the role in political processes and the further disappearance of the dynasty. The book is written on the basis of a large number of archival documents, mainly from the Russian State Archives of Ancient Acts (RGADA). It allowed reconstructing the rich tapestry of the Kuchumovichi’s life in Siberia and the Moscow state based on the methods and traditions of political history, studies of everyday life, prosopography, microhistory and genealogy. On the one hand, the book will be important for studies of Siberia, because the Siberian kings and princes in the Moscow state tried, if possible, to keep their familiar surroundings for a long time that preserved some distinctive features of their prior life’s period, which cannot be directly reconstructed with local materials. On the other hand, many nuances of the everyday life of these dynasts and their entourage can characterize not only the Siberian aristocracy but also the relevant layers of Moscow society as a whole, for which the Eastern traditions were also not immune to. Therein, we get an interesting slice of the Moscow society of the 16th–17th centuries: notably, the gradual forfeiture of the princes directly coincided with the exhaustion of the post-Horde and Eastern traditions in Russia as a whole. Despite some minor shortcomings, the materials of the monograph are so manifold so each reader will find in it some of his or her own interesting aspects, and will get an idea of an interesting slice of the Russian history of the 16th–17th centuries.